2020
DOI: 10.1016/s0140-6736(20)31014-x
|View full text |Cite
|
Sign up to set email alerts
|

Retinal findings in patients with COVID-19

Abstract: Tokyo, Japan) and XR Avanti SD-OCT (Optovue, Fremont, CA, USA).All patients showed hyper-reflective lesions at the level of ganglion cell and inner plexiform layers more prominently at the papillomacular bundle in both eyes (figure). Results of OCT-angiography and ganglionar cells complex analysis appeared normal. Furthermore, four patients presented subtle cotton wool spots and microhaemorrhages along the retinal arcade, observed on fundus examination, color fundus photography, and red-free imaging. Visual ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
486
4
20

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 480 publications
(560 citation statements)
references
References 4 publications
18
486
4
20
Order By: Relevance
“…Hence, it cannot be excluded that their ndings may be ascribed to pre-existing non-COVID-19-related systemic diseases affecting the retina, such as hypertensive or diabetic retinopathy or other infectious diseases. [40][41][42][43] In our cohort, largely composed of subjects with severe COVID-19, we merged retinal ndings with baseline anamnestic ndings. Nevertheless, our negative results should also be attributed to the ongoing immune modulating treatment, including steroids or tocilizumab, that could have concealed ophthalmoscopic ndings.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it cannot be excluded that their ndings may be ascribed to pre-existing non-COVID-19-related systemic diseases affecting the retina, such as hypertensive or diabetic retinopathy or other infectious diseases. [40][41][42][43] In our cohort, largely composed of subjects with severe COVID-19, we merged retinal ndings with baseline anamnestic ndings. Nevertheless, our negative results should also be attributed to the ongoing immune modulating treatment, including steroids or tocilizumab, that could have concealed ophthalmoscopic ndings.…”
Section: Discussionmentioning
confidence: 99%
“…However, the differences between the severe and critical groups suggest that patients with severe COVID-19 may have sustained varying degrees of cardiac damage as the disease progresses. Recent studies have also indicated that multiple serious sequelae persisted in patients who recovered from severe COVID-19 disease, including massive heart impairment [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it cannot be excluded that their ndings may be ascribed to pre-existing non COVID-19-related systemic diseases affecting the retina, such as hypertensive or diabetic retinopathy or other infectious diseases. [40][41][42] In our cohort, largely composed of subjects with severe COVID-19, we merged retinal ndings with baseline anamnestic. Nevertheless, our negative results should also be attributed to the ongoing immune modulating treatment, including steroids or Tocilizumab, that could have concealed ophthalmoscopic ndings.…”
Section: Discussionmentioning
confidence: 99%